Strategi Pengembangan Manajemen Bisnis Digital Berbasis Web untuk Mendukung Ketahanan Pangan Lokal di Sektor Perikanan Patin Kecamatan XIII Koto Kampar - Andri Nofiar. Am; Rahmad Akbar; M. Alkadri Perdana; Antoni Pribadi; M. Rukhsah (Universitas 45 Surabaya, 2025)
The rapid development of digital technology has created new opportunities for strengthening local economies, especially in rural areas with unique commodity potentials. This study aims to develop a digital business strategy to enhance the local economy based on the catfish (ikan patin) commodity in Kampung Patin. The research employs a qualitative descriptive approach using SWOT analysis to identify internal and external factors that influence the digital transformation of local entrepreneurs. Data were collected through interviews, field observations, and documentation involving fish farmers, business owners, and local government representatives. The results of the SWOT analysis reveal that community solidarity and product quality are the main strengths, while weaknesses include limited digital literacy and marketing capacity. Opportunities arise from the growth of e-commerce platforms and government support for digitalization programs, whereas threats come from increasing market competition and technological gaps. The findings suggest that strengthening digital marketing capabilities, building a collective brand identity, and developing a local e-marketplace can enhance competitiveness and promote sustainable economic growth in Kampung Patin.